2011
DOI: 10.1103/physrevb.84.035315
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical analysis of the crystal structure, band-gap energy, polarization, and piezoelectric properties of ZnO-BeO solid solutions

Abstract: The electrical properties, the spontaneous polarization, and the piezoelectric response of ZnO can be tailored by alloying ZnO with BeO for applications such as electrodes in flat panel displays and solar cells, blue and ultra-violet (UV) light emitting devices, and highly sensitive UV detectors. We present here the results of a study that employs density functional theory to analyze the crystal structure, the band structure, spontaneous polarization, and piezoelectric properties of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…5 More recently, recognizing the wurtzite hexagonal structure of BeO that has a wide bandgap (10.8 eV), Be x Zn 1−x O was proposed by Ryu et al as a candidate for the solar-blind devices. 27 In the previous studies, however, sizes of supercells were quite small such that the x values are limited to the multiples of 1/16 and 1/8, respectively. This is probably due to the phase separation and compositional fluctuation of Be in the Be x Zn 1-x O alloy.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…5 More recently, recognizing the wurtzite hexagonal structure of BeO that has a wide bandgap (10.8 eV), Be x Zn 1−x O was proposed by Ryu et al as a candidate for the solar-blind devices. 27 In the previous studies, however, sizes of supercells were quite small such that the x values are limited to the multiples of 1/16 and 1/8, respectively. This is probably due to the phase separation and compositional fluctuation of Be in the Be x Zn 1-x O alloy.…”
Section: Introductionmentioning
confidence: 93%
“…36. [25][26][27] Based on a search for the atomistic configurations with a supercell containing 32 atoms, Fan et al found that the Be x Zn 1−x O alloy favoured local phase segregation, where three kinds of crystallites with Be concentration values of x = 1/4, 1/2 and 3/4 arise. 5 More recently, recognizing the wurtzite hexagonal structure of BeO that has a wide bandgap (10.8 eV), Be x Zn 1−x O was proposed by Ryu et al as a candidate for the solar-blind devices.…”
Section: Introductionmentioning
confidence: 99%
“…The two Li Zn sites for each configuration are chosen among all the possible substitutional sites to ensure that the two V Zn have the lowest formation energy. We also find that the Li dopants and V Zn tend to stay close to each other, therefore the most stable sites of Li dopants for each configurations are as follows: (10,8), (3,7), (4,9), and (4,5). In order to find out the magnetic properties of V ZnZnO NW with Li-dopant, all models are fully relaxed, and these optimized Li-doped ZnO NWs with V Zn are subject to calculate magnetic properties of system.…”
Section: Resultsmentioning
confidence: 98%
“…[1]. As one of the II-VI low-dimensional nanomaterials, ZnO NW has been applied to photovoltaics, gas sensors, and field-effect transistors [2][3][4]. ZnO NW also possesses a large magnetic coercive force and high blocking temperature, which would be useful for fabricating nano-magnetic devices well [5].…”
Section: Introductionmentioning
confidence: 99%
“…This is unlike Mg x Zn 1Àx O alloys which are limited by a Mg mole fraction of x ¼ 0.38. 3,8 However, in principle, the phase instability of Be x Zn 1Àx O alloys could occur due to: (i) internal strain effect from different bond lengths between Zn-O (aand c-axis bond lengths: 1.97 Å and 1.99 Å ) and Be-O (a-and c-axis bond lengths: 1.65 Å and 1.66 Å ) and the subsequent lattice deformation of wurtzite structure; 9 (ii) a large difference in thermal expansion coefficients [2.49 and 3.98 Â 10 À6 K À1 (5.35 and 7.18 Â 10 À6 K À1 ) at 300 K and 700 K for c-axis ZnO (c-axis BeO), respectively]; 10 and (iii) substantial strain from the lattice mismatch between the alloy film and the underlying substrate, e.g., Al 2 O 3 (%18%) and Si (111) (%15%). 11 These can readily induce phase separation and compositional splitting in the ternary alloy system.…”
Section: O 3 (0001)mentioning
confidence: 99%